The first inspector general of civil buildings in Algeria Mr. CHARLES TEXIER (1845-1853) and his most outstanding achievements in the field of preserving and valuing the archaeological heritage - bouarour, chafika (The Algerian Historical Journal, 2026)
The article deals with the works of the first person to hold the position of Inspector General of Civil Buildings, Mr. Texier in charge of the preservation of historical monuments in Algeria, and his work between (1845-1853) his quest to defend the archaeological heritage, despite the restrictions imposed on him by the military officials; This article revolves five points: starting with the presentation of this personality, and the missions assigned to him by the Ministry of War, ending with the impact of his mission on the issue of the Algerian archaeological heritage